A comprehensive study on the maintenance of medical equipment at tertiary care hospital in India - Tadia, Vijay Kumar; Kharate, Samadhan (International Journal of Research in Medical Sciences, 2020)
Background: It is essential for any health-care facility, regardless of its size, to implement a maintenance programme for medical equipment. The maintenance not only has a positive impact on the safety and effectiveness of healthcare technology, but also increases the lifetime of equipment and thus helps to save scarce investment resources. It also enhances the demand for health services. Demand for services availability is crucial of functioning healthcare technology. Methods: A comprehensive descriptive study of the maintenance of equipment at a tertiary care corporate hospital in India from January 2012 to May 2012. A convenient sampling method was used to capture data from Key Participants which included two categories of staff viz technicians and managers/administrators. There were 40 technicians and 10 managers who responded to the questionnaire. Both the primary and secondary sources of data were used. Results: Breakdown data analysis showed that the major cause of breakdown was human errors. About 40% of breakdown that occurred in the hospital was mainly because of manual errors followed by electrical and mechanical issues. Average down time for the time period of 5 months came to around 19 hours, which was quite high. Analysis of KAP questionnaire showed that about 55% technicians were not having the educational qualification required for handling the medical equipment, about 15% were not given training at the time of purchase of the equipment. Similarly, few managers were not aware about maintenance practices and importance of maintenance management for smooth and efficient functioning. Conclusions: Good and effective maintenance practices can reduce the cost of maintenance of equipment that arises due to breakdown. The training of equipment users and maintenance managers reduces the equipment downtime. To reduce the possibility of equipment malfunction following service or repair, all personnel involved in maintaining and servicing equipment should be trained.